The impact of the nutrition situations and physical activities of academicians on anthropometric measurements and blood parameters - Kizilaslan, Nildem (Progress in Nutrition, 2022)
Background: This study was planned and carried out to determine the influence of nutrition situations and physical activity levels of individuals working as academicians at the university on their anthropometric measurements, blood glucose, and blood lipid. Materials and Methods: 47 volunteers participated in the research, and their height, waist circumference (WC), and weight was measured. The blood samples of the volunteers was taken after 12 hours of fasting, their preprandial blood glucose (PrBG), postprandial blood glucose (PoBG), total cholesterol, triglyceride, HDL-cholesterol, and LDL-cholesterol levels were measured. Nutritional consumption measurements were taken with 24-hour recall method, and, after having the volunteer subjects make nutritional changes, daily consumption quantities were determined. Results: The body mass index (BMI) was 24.34±4.73kg/m2 in the women and 27.90±3.97 kg/m2 in men. The mean WC was 84.15±15.89 cm for women and 98.18±10.89 for men. A statistically significant difference was found between the BMI of the women and their WC, total cholesterol level, HDL-cholesterol, LDL-cholesterol, and triglyceride averages. According to the BMI of the men, a statistically significant difference was found with their WC, PoBG, and triglyceride averages. In both women and men, it was observed that as their physical activity increased, their levels of BMI, WC, PoBG level, and triglyceride level were reduced. Conclusions: We conclude from this study that academicians who are overweight and who suffer from impaired glucose intolerance and dyslipidemia have balanced nutrition and to do physical activities to become healthy.